The Stability Study of Electrochemical Aptasensor to Detect SARS-CoV-2 Spike Protein and Its Application for Clinical Samples of Nasopharyngeal Swab - Arum Kurnia Sari; Ghina Nur Fadhilah; Irkham Irkham; Muhammad Yusuf; Shabarni Gaffar; Yeni Wahyuni Hartati (Indonesian Journal of Chemistry, 2023)
The stability characteristics associated with the shelf life of a biosensor are rarely investigated, however, they are important factors for real applications. Stability is the variation in the detection signal over a long period of storage. This study aims to determine the effect of storage time on the stability of SARS-CoV-2 receptor binding domain (RBD) spike protein aptamers related to shelf life and the performance of an electrochemical aptasensor on clinical samples. The research method includes a stability study conducted using the accelerated stability method based on the Arrhenius equation at three variations of temperature and storage time. The electrochemical aptasensor's performance was evaluated on clinical samples of 32 nasopharyngeal swabs at biosafety level 3 and its potential on clinical saliva samples. The results indicated that the developed electrochemical aptasensor was stable for ± 15 days with a shelf life of 18, 17 and 16 days, respectively, at 25, 40 and 50 °C. This electrochemical aptasensor has the potential to be a Point of Care (POC) device for the clinical detection of SARS-CoV-2 because it can be tested on clinical samples of nasopharyngeal swabs and the results show its potential application to detect in clinical saliva samples.